Research on the influence mechanism of safety risk factors on traffic organization of high-speed railway construction. Issue 1 (January 2021) - Shen, Zebin; Zhang, Meijie; Liu, Yiyang; Jiang, Chunlin
Abstract: In the development of high-speed railway construction, the high-speed railway construction scheme and technology are constantly improved. Nowadays, the high-speed railway construction mainly relies on the traffic organization of the railway to organize the transportation of prefabricated components and carry out hoisting. In the process of traffic operation organization of railway engineering, the construction company often faces many safety risks. Therefore, it is of great significance to analyze the influence mechanism of various risk factors on the operation and safety of Railway Engineering and put forward corresponding suggestions. In this paper, through literature analysis and expert interviews, nine key factors are selected. The safety risk factors are divided from four dimensions of personnel, machinery, management and environment. The importance of these risk factors is ranked by AHP, and Through the method of interpretative structural model, this paper uses these nine key factors to build a five layer interpretative structural model, and uses interpretative structural model to analyze the influence mechanism of safety risk factors on driving organization safety.